The press, anti-alienism, and the Jewish community in First World War Scotland. Issue 2 (4th May 2018) - Hansen, Kirk
ABSTRACT: Strained relations between Scots and Jews during the First World War have largely been forgotten thanks in great part to post-war Jewish displays of patriotism combined with an oversight of wartime tension within the existing historiography. With few sources covering this issue, the Scottish press presents itself as a vital resource because of its heightened wartime readership and since it provided an outlet for both the host and Jewish communities to vent their respective frustrations. This article will survey a number of Scottish papers to show how the widespread anti-alien attitudes during the war affected the Jewish community.